On the Design of Dual-Polarised Linear Antenna Arrays with Enhanced Port-to-Port Isolation - Dariusz Wójcik; Maciej Surma; Artur Noga; Mirosław Magnuski (Sensors, 2020)
The paper describes the process of designing a dual-polarised linear antenna array with enhanced port-to-port isolation, with the example of a four-element array with isolation better than 60 dB for the U-NII 5.15–5.925 GHz band. As a single antenna, dual-polarised electromagnetically coupled microstrip antennas were used with port-to-port isolation not exceeding 25 dB. A significant improvement in the isolation of the array was achieved thanks to the application of a dedicated feeding network. On the basis of theoretical analysis, a mathematical model describing port-to-port isolation was developed. Circuit and full-wave simulations were carried out to show the influence of electromagnetic couplings between antennas and/or the microstrip lines of the feeding network and the selection of phase shifters/power dividers on the isolation. The fabricated prototype is characterised by a gain of about 14 dBi, polarisation purity of at least −27 dB within the main lobe and close to expectations isolation better than 57 dB within the whole operational band.